2018
DOI: 10.1111/eea.12712
|View full text |Cite
|
Sign up to set email alerts
|

Limited genetic evidence for host plant‐related differentiation in the Western cherry fruit fly, Rhagoletis indifferens

Abstract: The shift of the fruit fly Rhagoletis pomonella (Walsh) in the mid-1800s from downy hawthorn, Crataegus mollis (Torrey & Asa Gray) Scheele, to introduced domesticated apple, Malus domestica (Borkhausen), in the eastern USA is a model for ecological divergence with gene flow. A similar system may exist in the northwestern USA and British Columbia, Canada, where Rhagoletis indifferens Curran (Diptera: Tephritidae) attacks the native bitter cherry Prunus emarginata (Douglas ex Hooker) Eaton (Rosaceae). Population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In this regard, the nuclear-encoded microsatellites imply that host association significantly affects patterns of genetic divergence and, by inference, generates ecologically based RI and induces speciation in R. cingulata group flies (Figure 2 and Figure 3; Table 2). In previous studies, Maxwell et al [25], Smith et al [24] and Saint Jean et al [26] found little evidence for genetic differentiation between native and domesticated cherry-infesting populations of R. cingulata or R. indifferens . However, here we have shown that genetically distinct forms of R. cingulata group flies exist on non-cherry host plants, including native olives and muttonwood, in areas of geographic overlap (sympatry) with the cherry-infesting species R. cingulata .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, the nuclear-encoded microsatellites imply that host association significantly affects patterns of genetic divergence and, by inference, generates ecologically based RI and induces speciation in R. cingulata group flies (Figure 2 and Figure 3; Table 2). In previous studies, Maxwell et al [25], Smith et al [24] and Saint Jean et al [26] found little evidence for genetic differentiation between native and domesticated cherry-infesting populations of R. cingulata or R. indifferens . However, here we have shown that genetically distinct forms of R. cingulata group flies exist on non-cherry host plants, including native olives and muttonwood, in areas of geographic overlap (sympatry) with the cherry-infesting species R. cingulata .…”
Section: Discussionmentioning
confidence: 99%
“…Fruits infested with larvae of R. cingulata species group flies were collected from 2004–2012 at sites across North America (Figure 1, Table 1). Microsatellite and mtDNA data for R. indifferens and R. cingulata were taken from Saint Jean et al [26] and Doellman et al [36]. New microsatellite and mtDNA sequencing data in the current study were generated from three non-cherry-infesting populations of R. cingulata group flies: R. chionanthi (site 18, collected from fringe-tree at Perry, Georgia), R. osmanthi (site 19, collected from tea-olive at Lake Lizzie, Florida), and R. turpiniae (site 20, collected from muttonwood at Xalapa, Veracruz, Mexico).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotyping was performed as described in Saint Jean et al. (2018), with size standards included in each genotyper run, as well as representative eastern R. cingulata and western R. indifferens , to ensure that alleles were properly aligned and comparably scored. Details of the methods used for microsatellite data analysis are given in the .…”
Section: Methodsmentioning
confidence: 99%